A Contextual Framework for the Development of a Building Sustainability Assessment Method for Iran. Issue 2 (1st June 2016) - Malek, Shahrzad; Grierson, David
Abstract : As one of the fastest growing countries in the Middle East, and the one most vulnerable to climate change, the main challenge now facing Iran today is how to house its growing population in a socially, economically, and environmentally sustainable way. However, in the absence of a national framework to guide the sustainable development of the built environment, responding to this challenge is problematic. The articulation of a comprehensive assessment method that would enable issues of sustainability to be addressed and incorporated within building construction projects is urgently required. The research that underpins this paper takes account of current tools in aiming to support the development of a national building sustainability assessment method (BSAM) for use in Iran that involves the identification of sources of impact, specific benchmarks, and priorities for a weighting system for assessment criteria. This paper profiles the basis of a contextual framework that will inform the development of such a regional-based tool, taking account of Iran's current climate change adaptation policies and priorities, its environmental conditions and socio-economic challenges, building typologies, standards and benchmarks.